Is Work Motivation Important? The Role of Work Motivation to See the Consistency of Grit Influence on Individual Work Performance: English - Syukri Santoso; Siti Aisyah; Suryani Hardjo (Ilomata International Journal of Social Science, 2026)
This study aims to analyze the contribution of work motivation on the influence of grit on individual work performance. This research conducted quantitative non-experimental. The sample in this study amounted to 60 police personnel. Data were collected using three scales adopted from previous research. The results direct effect indicate it has been observed that grit exerts a significant influence on individual work performance, with an estimated value of 0.503. This influence is categorized as "strong" due to its magnitude, which exceeds 50%. The indirect effect is characterized by the influence of grit on individual work performance through motivation. Indirect effect has a lower value than the direct effect of 0.303, representing an effect size of approximately 30.3%. In the overall path analysis, it is evident that the strongest path is observed to be the influence of grit on work motivation, with a significant proportion of 65.8%. The correlation between work motivation and grit, with individual work performance is not particularly robust. Consequently, it can be deduced that motivation has the potential to enhance individual work performance, superseding the notion that grit is the sole contributor. The study provides a comprehensive overview of the research deficiencies and recommendations.